2013
DOI: 10.1155/2013/276498
|View full text |Cite
|
Sign up to set email alerts
|

NSOM/QD-Based Visualization of GM1 Serving as Platforms for TCR/CD3 Mediated T-Cell Activation

Abstract: Direct molecular imaging of nanoscale relationship between T-cell receptor complexes (TCR/CD3) and gangliosidosis GM1 before and after T-cell activation has not been reported. In this study, we made use of our expertise of near-field scanning optical microscopy(NSOM)/immune-labeling quantum dots- (QD-)based dual-color imaging system to visualize nanoscale profiles for distribution and organization of TCR/CD3, GM1, as well as their nanospatial relationship and their correlation with PKCθ signaling cascade durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In T cells, the lipid rafts can isolate on membrane microdomains the GM1 ganglioside (lipid raft marker), the phosphatidylinositol 4,5-bisphosphate (PIP 2 ), GPI-linked proteins, Src family kinases and GTP binding proteins (Janes et al 2000). Disruption of lipid rafts by depleting cholesterol-using methyl-β-cyclodextrin (MβCD) affects TCR/CD3 clustering and cytokine secretion (Blank et al 2005;Zhu et al 2011;Zhong et al 2013). Our findings point to a potential and specific role of GD2 in TCR clustering or signaling and as a constitutive element of lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…In T cells, the lipid rafts can isolate on membrane microdomains the GM1 ganglioside (lipid raft marker), the phosphatidylinositol 4,5-bisphosphate (PIP 2 ), GPI-linked proteins, Src family kinases and GTP binding proteins (Janes et al 2000). Disruption of lipid rafts by depleting cholesterol-using methyl-β-cyclodextrin (MβCD) affects TCR/CD3 clustering and cytokine secretion (Blank et al 2005;Zhu et al 2011;Zhong et al 2013). Our findings point to a potential and specific role of GD2 in TCR clustering or signaling and as a constitutive element of lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…However, phosphoantigens induce the clustering and co-localization of the human V𝛾9V𝛿2 TCR and the lipid raft associated lipid GM1, 96 a feature that has been reported for the activated 𝛼𝛽 TCR as well. 97 Thus, activation induced changes in the lipid environment of the 𝛾𝛿 TCR can be assumed as well and might be involved in the regulation of ITAM accessibility.…”
Section: Allosteric Regulation Of the Tcr's Conformationmentioning
confidence: 99%
“…Following this accumulation of substrate, a variety of disease states with different symptoms occur in the patient. 37,38 According to the latest data collected until 2021, 51,52 Depending on the type of mutation, the symptoms of the disease will also be different, that is, the severity of the mutations is directly related to the age of onset of the disease. 53 For example, one study found that F I G U R E 1 Some important mechanisms in the pathogenesis of GM1 gangliosidosis (The CT scan image of the brain is taken from the study of Nicoli et al 18 ).…”
Section: Significance Statementmentioning
confidence: 99%
“…As mentioned earlier, in patients with GM1 gangliosidosis due to a mutation in the glb1 gene, enzyme activity is lost and the enzyme deficiency causes the accumulation of substrate in body tissues and increases urinary metabolites. Following this accumulation of substrate, a variety of disease states with different symptoms occur in the patient 37,38 . According to the latest data collected until 2021, Rha et al have classified the main mechanisms of GM1 disease into five important categories, which include the process of apoptosis through the UPR, neurotransmission, autophagy, neurotrophic factor activity, and neuroinflammation 39 .…”
Section: Introductionmentioning
confidence: 99%